Helping the helpers : altruism as a rational choice of donors to a students voluntary organization (2009)
Altruism, understood as the individual disposition to sacrifice personal income to improve someone else's income can be a rational choice strategy which responds to different motivations, incentives and institutions, in a consistent way with the donor's optimization logic. In this article we extend the Andreoni and Miller's experimental design (2002) using a modified Dictator game and we applied it to 470 students from several universities and different majors, years of study and level of income who can donate part of their income to the Bella Flor Foundation (http://www.bellaflor.org/), a real nonprofit organization founded by a group of college students whose mission is "to promote the integral development of the children from Bella Flor, Paraíso and Mirador neighborhoods through social activities in education, health care, recreation, and exalting human values". We test the consistency of the player's decisions with the axioms of revealed preferences, and with the effects of relative prices and income. We also evaluate the violation of consistency of the axioms and estimate the demand functions for altruism towards this charity, with policy implications related to the optimal design for fundraising strategies. Our results confirm that a significant fraction of individuals show consistent decisions, i.e. that donations to these charities behave as "normal goods" in price and income effects and with rather small number of violations of the axioms of revealed preferences. However, the experimental data suggests that revealing the identity of the donor can decrease altruism and induce more violations of the axioms of consistent behavior mentioned.